Enhancing Student Achievement through a Digital Learning Module: The TEFA-T Model in a Teaching Factory of Automotive Vocational Education - Hasan Maksum; Wawan Purwanto; Siman; Selamat Triono; Hanapi Hasan, (International Journal of Interactive Mobile Technologies (iJIM), 2025)
This study is based on preliminary studies that identified the problem of suboptimal learning quality. The objective of the study is to develop a digital e-module within the teaching factory (TEFA) (TEFA)-T learning model as an effort to improve the academic achievements of automotive vocational students, ensuring the module is valid, practical, and effective. The study method is research and development (R&D) using the Instructional Development Institute (IDI) model development procedure, which consists of three stages: define, develop, and evaluate. The results of this study generally produce a comprehensive digital learning e-module design consisting of a cover, preface, table of contents, learning structure, learning patterns, e-module position map in learning, glossary, learning introduction, learning activities, evaluation, and closing. The TEFA-T learning e-module is statistically validated and practical. The average Aiken’s V value obtained is 0.967, indicating that the digital e-module content is in the valid category. The TEFA-T learning e-module is considered very practical, as shown by the average practicality assessment scores of 92.20% from lecturers and 90.60% from students, both in the “Very Practical” category. In conclusion, after implementing the TEFA-T learning e-module, students can build knowledge inductively and deductively, as well as gain learning experiences through one-way interaction, personal interaction, and effective learning interaction, significantly improving student academic achievement (Sig. 2-tailed value is less than 0.05).